The Impact of Blockchain on Accounting Information Systems - Zeyad Hashim ALSaqa; Ali Ibrahim Hussein; Saddam Mohammed Mahmood (Journal of Information Technology Management)
The objective of the research is to clarify what Blockchain technique is and the developments of its various uses, and identify the accounting perspective of this technique and the possibility of using it in accounting work. It also aims at demonstrating how to utilize its Blockchain technique in accounting information systems, and identify the most important potential effects of the use of technique in accounting information systems. To achieve the research objectives, a descriptive approach was adopted to discuss the fundamentals of Blockchain technique and its most important accounting implications, in addition, its significance for the usefulness and reliability of the development of automated computing accounting systems. The researchers concluded that the use of Blockchain technology for accounting work requires analysis of the related impact on the development of accounting information systems in terms of their implementations and modules, with the need to fully transition in the design of accounting information systems to electronic sophisticated programs and applications developed and technologically advanced.